3x+33=6

Simple and best practice solution for 3x+33=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+33=6 equation:



3x+33=6
We move all terms to the left:
3x+33-(6)=0
We add all the numbers together, and all the variables
3x+27=0
We move all terms containing x to the left, all other terms to the right
3x=-27
x=-27/3
x=-9

See similar equations:

| 5b-8/3=24 | | 11d-6d=25 | | 3x/7=2x/3-1/3. | | 3(a+8)=6×10+6 | | x/3+5=2*x | | 1=-8+(x/2) | | 18-5f=2f+4. | | -2=-4x+17 | | 2m=(3/4)+4 | | -5x-21=1 | | 5z-108=113 | | 6*x-7+x=77 | | 9x=4x+180-7x | | 6k-k=27-4’ | | –5x=–35 | | 4(x+5)-9=11-2(x-3) | | 3x/2x-28/2x=1 | | 2x/3+3x/2=x/4-13/12 | | 6p=2p-8 | | -1e+2=3 | | 107+135+78+x=360 | | 4e-4=1e+5 | | 8x+9=11x-15 | | 1.5/3=1/x | | x–4=–12 | | 4x-2+8=3x+6+x | | 4e+2=6 | | x+x+1=15-x+2 | | X-140=0.3x | | Y=4075+0.3Y-20r | | 9x+3=-87 | | 7*x=x+78 |

Equations solver categories